2017
DOI: 10.1093/annonc/mdx050
|View full text |Cite
|
Sign up to set email alerts
|

A need to simplify informed consent documents in cancer clinical trials. A position paper of the ARCAD Group

Abstract: BackgroundIn respect of the principle of autonomy and the right of self-determination, obtaining an informed consent of potential participants before their inclusion in a study is a fundamental ethical obligation. The variations in national laws, regulations, and cultures contribute to complex informed consent documents for patients participating in clinical trials. Currently, only few ethics committees seem willing to address the complexity and the length of these documents and to request investigators and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…The decisional conflict scale developed by O'Connor examines several elements including lack of information about alternatives and their consequences, unclear values, and lack of support or advice [13]. The 16-item scale is scored on a Likert scale ranging from 'strongly disagree' (6) to 'strongly agree' (0). A low score on the decisional conflict scale indicates less decisional conflict about choosing whether to participate in genome sequencing.…”
Section: Decisional Conflict Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The decisional conflict scale developed by O'Connor examines several elements including lack of information about alternatives and their consequences, unclear values, and lack of support or advice [13]. The 16-item scale is scored on a Likert scale ranging from 'strongly disagree' (6) to 'strongly agree' (0). A low score on the decisional conflict scale indicates less decisional conflict about choosing whether to participate in genome sequencing.…”
Section: Decisional Conflict Scalementioning
confidence: 99%
“…More broadly beyond genome sequencing studies, efforts have commenced to reduce the complexity of consent information provided to prospective participants in a variety of research contexts [6,7]. Prior research has found that many individuals fail to comprehend consent information [8], and that consent documents have increased in length over time, with concerns raised that long consent forms are less likely to be read [9].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an excess of information that becomes unmanageable and prevents investigators from being effectively updated on the safety of investigational drugs. Another example is the high number of informed consent versions generated in some studies and their complexity, which are difficult to understand by patients, 11 and may even generate distrust of the study and the research team.…”
Section: Growth Of the Burden Of Bureaucracy In Clinical Researchmentioning
confidence: 99%
“…Adequate procedures, such as interpreting and periodically summarising the available information, should be evaluated. ECRO will employ the following methods to attain its objectives (box 1): 12 ; the occurrence and causes of excessive delays in starting treatment in cancer patients due to centralised molecular testing [13][14][15] ; the broadening of eligibility inclusion criteria in clinical trials, to avoid disparities in care [16][17][18] ; the consequences of outsourcing the monitoring of trials 7 ; the need to simplify informed consents 11 and so on. 3.…”
Section: Esmo Survey On the Administrative And Bureaucratic Burden Inmentioning
confidence: 99%
“…Researchers have suggested that clinical trial consent forms do not adhere to best practice recommendations. Evidence shows medical jargon, and the overwhelming nature of information provided limits the value of the consent form as a source of patient decision making (Bleiberg et al., 2017). In a study analysing 13 cancer trial consent forms covering phase I, II and III trials, the average word count was 4,562 words or 18 pages (2,644–6,977 words, 11–28 pages).…”
Section: Introductionmentioning
confidence: 99%